Everyday utopias and social reproduction - Salmenniemi Suvi; Ylöstalo Hanna (SAGE PUBLICATIONS LTD, 2025)
This article analyses reproductive labour in everyday utopias. Everyday utopias refer to spaces and practices that experiment with alternative forms of life and create new social imaginaries. Drawing on ethnographic research in three everyday utopias in Finland, the article argues that labour plays a key role in transformative politics by prefiguring socially and ecologically sustainable forms of life not conducive to capitalist logic. The article brings together feminist social reproduction theory and utopian studies to shed light on different forms of reproductive labour in everyday utopias. It identifies four forms of labour: manual, affective, mnemonic and experimental. In particular, experimental labour foregrounds the importance of everyday utopias as sites of political imagination in which novel forms of life are actively developed and tried out. The article concludes by suggesting that everyday utopias subvert conventional understandings and practices of labour and social reproduction.